PHB synthase from Streptomyces aureofaciens NRRL 2209 - Ramachander, TVN; Rawal, SK (FEMS Microbiology Letters, 2005)
An similar to4.9 kb Sau3A I genomic DNA fragment from the Streptomyces aureofaciens NRRL 2209 aiding in the biosynthesis of PHB in recombinant Escherichia coli has been sequenced and analysed for phaC gene. The putative phaC(sa) gene of 2 kb is 79.1% GC rich and encodes a 63.5 kDa protein. It expressed under its own promoter and significant PHA synthase activity was detected in the recombinant E coli. This is the first putative PHA synthase gene reported from a Streptomyces sp. with serine as the active nucleophile in the conserved lipase box. The phaC(sa) was found in close proximity to a regulatory gene, which apparently regulated the phaC expression. (C) 2004 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.
Keywords: PHA synthase; PHB; Streptomyces